EXTRACRANIAL METASTASIS OF GLIOBLASTOMA: A RARE CASE - Rahmawati, Dessika; Marhaendraputro, Eko Arisetijono; Kurniawan, Shahdevi Nandar; Wirathmawati, Andina (Malang Neurology Journal, 2019)
Glioblastoma is the most common primary malignant tumor in the neural tissue and a highly aggressive primary tumor in human. It involves glial cells in 52% of functional brain tissue cases and 20% of all intracranial tumors. Extra cranial metastasis of Glioblastoma is very rare. Metastasis outside CNS was uncommon in GBM but it could occur with frequency 0.2% and can spread in head and neck sites. The mechanism of this spread is not understood yet. The extracranial spread routes were speculated on the direct lymphatic connections, the venous system and the adjacent structure like dura and bone. We present a case of female patient with a known glioblastoma who had an extracranial metastasis on her left neck with complete Radiotherapy n Chemotherapy and survive more than 2 years.